Javni sektor so ljudje - Počivavšek, Jakob Krištof (Delavci in delodajalci, 2026)
The paper examines the elements of quality jobs, the priorities that matter to employees, and the measures that motivate employees at work and influence them to stay with a particular employer or choose to work for them. Pay is only one of these elements, although it is typically at the forefront of discussions on employee satisfaction, while other elements that define job quality are often unjustifiably placed in the background.
Keywords: kakovostna delovna mesta; leadership; odnosi na delovnem mestu; plače v javnem sektorju; pogoji dela; quality jobs; vodenje; wages in public sector; working conditions; workplace relationships